Utilization of clinical practice guidelines and interprofessional collaboration in depression management in Swiss primary care: a cross-sectional survey study among primary care physicians - Karin Mayer; Christoph Merlo; Stefan Markun; Stefan Neuner-Jehle; Patrick E. Beeler (BMC Primary Care)
Abstract Objectives To (i) investigate the current state of depression management in Swiss primary care post-COVID-19, focusing on the utilization of guidelines or associated tools, (ii) explore potential associations with depression management, and (iii) evaluate availability of and communication with psychiatrists and psychotherapists. Methods A previously developed self-report questionnaire, covering screening, diagnosis, management, and interprofessional collaboration, was distributed online, with a supplementary paper version, to 168 Swiss primary care physicians (PCPs) participating in the Swiss Sentinel Surveillance System. Multivariable logistic regressions explored associations. Results Of the 168 primary care physicians invited to participate, 116 completed the survey (response rate: 69%). Among these, 61% utilized guidelines for depression management, with statistically significant associations towards increased guideline utilization for PCPs with some psychiatric training as residents (odds ratio [OR] 4.13; 95% confidence interval (95% CI) 1.27, 16.02) and decreased utilization for the age group 60–81 (OR 0.29; 95% CI 0.09, 0.93). Guideline utilization was associated with perceived competency in prescribing antidepressants (OR 3.51; 95% CI 1.21, 11.08). The majority reported difficulties in organizing therapy with mental health specialists and rarely received feedback after patient referrals. Conclusion While the utilization of guidelines among participants was inconsistent, over 60% indicated using either guidelines, tools, or both. The study highlights systemic issues in interprofessional collaboration between PCPs and mental health specialists that require attention.